2017
DOI: 10.1186/s12864-017-3852-x
|View full text |Cite
|
Sign up to set email alerts
|

Coping with living in the soil: the genome of the parthenogenetic springtail Folsomia candida

Abstract: Background Folsomia candida is a model in soil biology, belonging to the family of Isotomidae, subclass Collembola. It reproduces parthenogenetically in the presence of Wolbachia, and exhibits remarkable physiological adaptations to stress. To better understand these features and adaptations to life in the soil, we studied its genome in the context of its parthenogenetic lifestyle.ResultsWe applied Pacific Bioscience sequencing and assembly to generate a reference genome for F. candida of 221.7 Mbp, comprising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
150
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(160 citation statements)
references
References 83 publications
(112 reference statements)
9
150
1
Order By: Relevance
“…Their great abundance, low vagility, long‐term local persistence, and remarkable ecological specificity renders springtails excellent sources of information for inferring biogeographic processes (Garrick, Rowell, Simmons, Hillis, & Sunnucks, ). However, there are both technical and practical limitations to their use for biogeography, including but not restricted to (a) low single‐specimen DNA yields via modern extraction methodologies hinders opportunities for population‐level genomic‐scale analyses; (b) rampant cryptic speciation throughout Class Collembola, renders a priori taxonomic sampling for DNA extraction difficult, if not impossible; (c) limited taxonomic and gene coverage of available reference sequences—genomic datasets have only recently become available for three species (Faddeeva‐Vakhrusheva et al., , ; Wu et al., ); and (d) the dearth of financial resources devoted to springtail research despite their ecological and evolutionary importance. These limitations are reflected in the small molecular datasets (relative to modern genomic standards) and reliance of mitochondrial markers for springtail phylogeography.…”
Section: Discussionmentioning
confidence: 99%
“…Their great abundance, low vagility, long‐term local persistence, and remarkable ecological specificity renders springtails excellent sources of information for inferring biogeographic processes (Garrick, Rowell, Simmons, Hillis, & Sunnucks, ). However, there are both technical and practical limitations to their use for biogeography, including but not restricted to (a) low single‐specimen DNA yields via modern extraction methodologies hinders opportunities for population‐level genomic‐scale analyses; (b) rampant cryptic speciation throughout Class Collembola, renders a priori taxonomic sampling for DNA extraction difficult, if not impossible; (c) limited taxonomic and gene coverage of available reference sequences—genomic datasets have only recently become available for three species (Faddeeva‐Vakhrusheva et al., , ; Wu et al., ); and (d) the dearth of financial resources devoted to springtail research despite their ecological and evolutionary importance. These limitations are reflected in the small molecular datasets (relative to modern genomic standards) and reliance of mitochondrial markers for springtail phylogeography.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Faddeeva‐Vakhrusheva et al . (), our manual phylogenetic analysis of genes that code for nonribosomal peptide synthases did not point towards an HGT scenario (Supporting Information Table S1). Our phylogenetic reconstructions aligned with other studies that show a wide, albeit sporadic, phylogenetic distribution of nonribosomal peptide synthases, including the Arthropoda and Nematoda phyla (Wang et al ., ).…”
Section: Discussionmentioning
confidence: 92%
“…In contrast to prokaryotes, the functional impact of an HGT event into an animal recipient on its subsequent evolutionary trajectory generally remains unclear (Crisp et al ., ). Within insects, HGT from microbial genetic sources seems to have been formative in the evolution of many of their phytophagous and detritivorous feeding strategies (Faddeeva‐Vakhrusheva et al ., ; Wybouw et al ., ; Wu et al ., ). Studies in plant‐feeding insects have shown that the enzymatic assimilation of certain plant metabolites is facilitated by the lateral acquisition of microbial genes.…”
Section: Introductionmentioning
confidence: 99%
“…The combined genomic data for F. candida (DK) from Faddeeva‐Vakhrusheva et al . () and our laboratory (unpublished data) were used as the reference for the transcriptome analyses. The genome index was built using Bowtie2 (Langmead and Salzberg, ), and the reads were mapped using Tophat2 (Kim et al , ).…”
Section: Methodsmentioning
confidence: 99%